New methods in diagnosis and therapyOptimal treatment of coronary-to-pulmonary artery fistula: surgery, coil or stent graft? - Wejner-Mik, Paulina; Lipiec, Piotr; Peruga, Jan Zbigniew; Jaszewski, Ryszard; Pawłowski, Witold; Kasprzak, Jarosław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We report a case of a 57-year-old man with typical angina due to a coronary artery-to-pulmonary artery fistula, which was evident on transthoracic and transesophageal echocardiography with color Doppler flow mapping. The diagnosis was confirmed by coronary angiography. The patient underwent surgical ligation of the fistula. However, repeated transesophageal echocardiography and coronary angiography revealed persistence of the fistula with significant left-to-right shunt. The orifice of the fistula was then obliterated by stent-graft implantation, which was proven successful by angiography and echocardiography.